HUBUNGAN GANGGUAN KECEMASAN TERHADAP KEJADIAN MIGRAIN PADA MAHASISWA KEDOKTERAN: SYSTEMATIC REVIEW - Meta Zulyati Oktora; Debie Anggraini; Sari Oktavia; Rizky Mar Atusholeha; Salsabilla Umairah (Yayasan Nusantara Hasana Berdikari, 2025)
Migraine is a common neurological condition that significantly impacts the academic performance and quality of life of medical students. Anxiety disorders, often triggered by academic stress, are recognized as major contributors to the onset and exacerbation of migraine episodes. Comorbid mental health conditions such as anxiety and depression further increase migraine-related disability. This systematic review employed a qualitative meta-synthesis approach in accordance with the PRISMA 2020 protocol. Relevant articles published between 2019 and 2024 were retrieved from PubMed and EBSCO databases using keywords such as “anxiety disorder,” “migraine,” and “medical students.” The selected studies were screened based on defined inclusion criteria focusing on qualitative data and mental health correlations. Five eligible studies were included in the final analysis. All studies demonstrated a significant association between anxiety and migraine among medical students. Academic stress was identified as a key contributing factor, with female students showing higher susceptibility. The coexistence of anxiety and depression was associated with increased frequency, intensity, and disability due to migraine. There is a strong correlation between anxiety disorders and migraine among medical students. This comorbidity negatively affects both academic performance and mental health. Psychological interventions and stress management strategies are essential to improve students' quality of life and academic resilience.